Florence Adler Swims Forever - Beanland, Rachel (New York : Simon & Schuster, 2020)
"Atlantic City, 1934. Every summer, Esther and Joseph Adler rent their house out to vacationers escaping to "America's Playground" and move into the apartment above their bakery. The apartment is where they raised their two daughters, Fannie and Florence, and, despite the cramped quarters, it still feels like home. Now Florence has returned from college, determined to spend the summer training to swim the English Channel, and Fannie, pregnant again after recently losing a baby, is on bedrest, leaving her young daughter Gussie in Esther's care. After Joseph insists they take in a mysterious young woman whom he recently helped emigrate from Nazi Germany, the apartment is bursting at the seams. Esther wants nothing more than to keep her daughters close and safe but some matters are beyond her control: there's Fannie's risky pregnancy-not to mention her always-scheming husband, Isaac-and the fact that Stuart Williams, the heir of a hotel notorious for its anti-Semitic policies, seems to be in love with Florence. When tragedy strikes during one of Florence's practice swims, Esther makes the shocking decision to keep the truth about Florence's death from Fannie-at least until the baby is born. She pulls the rest of the family into an elaborate web of secret-keeping and lies, forcing to the surface long-buried tensions that show us just how quickly the act of protecting those we love can turn into betrayal. Told with humor and tenderness and based on a true story, Beanland's debut is a breathtaking meditation on the lengths we go to in order to keep our families together. At its heart, it is an uplifting portrayal of how the human spirit can endure-and even thrive-after tragedy"--.